Digital activist movements for energy resources: The case of Greenpeace Turkey - Gezmen, Başak (Springer Nature, 2022)
In this study, it is evaluated energy-related Twitter posts of Greenpeace Turkey, which is one of the most important and active NGOs in Turkey. The examples of tweet contents are investigated to the popularity ranking of the twitter account made on 10.08.2021 as the Greenpeace Turkey Twitter Account Energy-themed posts. All contents shared with “energy” word, which is searched as keyword from Twitter account, is the subject of the research. In the scope of the study, it is discussed on which topics Greenpeace Turkey’s energy-related posts focus on. Moreover, it is appraised activist movements on energy issues with their results and suggestions.
Keywords: Greenpeace Turkey; Digital Activist Movements; Energy Resources